EFFECT OF HUMAN MILK ON DEVELOPMENT OF RETINOPATHY OF PREMATURITY - Fatima, Bushra; Chisti, Akmal Laeeq; Sadiq, Muhammad Ali; Fatima, Tehreem; Karamat, Muhammad Irfan (Pakistan Armed Forces Medical Journal, 2019)
Objective: To determine the protective effect of human milk on development of retinopathy of prematurity (ROP) in preterm babies.Study Design: Observational study.Place and Duration of Study: King Edward Medical University Lahore, Department of pediatrics over a period of 11 months, from Feb 2016 to Dec 2016.Material and Methods: A total 142 preterm babies with birth weight